Cognitive Ergonomics: Supporting Effective Use of Predictive Analytics Using Ethical Mental Frameworks. Issue 182 (26th May 2020) - Colver, Mitchell
Abstract: As we become increasingly acquainted with the rich opportunities that analytics systems can provide, there is a commensurate need to consider the extent to which analytics tools are effectively integrated, with proper training, into the day‐to‐day functioning of higher education professionals. This chapter explores the extent to which predictive analytics can be properly scaffolded using robust cognitive ergonomics —mental frameworks of ethical and appropriate use—to support successful deployment of analytics in higher education.